Ranking and Relative Efficiencies of India’s Central Universities through the Lens of DEA - Gayang, Fullstar Lamin; Ravikumar, S. (Information Research Communications, 2025)
Aim/Background Universities are the cornerstone of a nation’s scientific and technical advancements. This study aims to evaluate the performance efficiency of India’s ten central institutions of higher learning using Data Envelopment Analysis (DEA). Unlike traditional methods that use fundamental performance ratios, this research adopts a multi-input, multi-output technique to provide an additional instrument for benchmarking and assessing decision-making units (organizations). Materials and Methods We employed the DEA super-efficiency model to compare the relative efficiency of ten central universities using NIRF data from 2020, 2021, and 2022. Input variables included total number of faculty, students, capital and operational expenditure, while output variables comprised graduates (UG, PG, Ph.D.), placements, publications, and citation count from Scopus and Web of Science. Results According to our data analysis, Jamia Millia Islamia University was the most efficient university among the ten institutions studied. The remaining nine universities demonstrated inefficiency to varying degrees, with efficiency scores fluctuating across the three-year period. Discussion The study reveals significant variations in efficiency scores across universities and over time, highlighting the complex interplay of factors influencing university performance. The inclusion or exclusion of specific input variables significantly affects efficiency scores, emphasizing the importance of considering institutional context when interpreting results. Conclusion DEA provides valuable insights for university management and policymakers, offering a multi-criteria approach for evaluating higher education institutions. This alternative analysis provides a new perspective for improving university standards and rankings, particularly as government funding is tied to efficient resource utilization.
Keywords: Efficiency; Central Universities; Data Envelopment Analysis.